The Role of Learning Motivation in Mediating the Influence of the School Environment, Parents, Peer Care Patterns on Learning Achievement - Ni’mah, Siti Khoirun; Wahyudin, Agus; Isnarto, Isnarto (Educational Management, 2021)
There are several factors that can improve learning achievement, namely internal and external factors. The purpose of this study was to determine the effect of the school environment, parenting styles, peers, learning motivation on learning achievement, the influence of the school environment, parenting styles, peers on learning motivation, the influence of learning motivation in mediating the school environment, parenting styles of parents, peers. on the learning achievement of elementary school grade 5 in Gebog Kudus. This study used an ex post facto research design. The results is: The positive and significant influence of the school environment on learning achievement was 6.81%, the parenting style of parents on learning achievement was 20.25%, peers on learning achievement were 8.58%, learning motivation on learning achievement was 6,25%, the school environment on learning motivation was 23.23%, the parenting style of parents on learning motivation was 18.49%, peers on learning motivation were 17.72%. Learning motivation can mediate positively and significantly the influence of parenting style on student achievement, tcount 2.1069 > from ttable 1.980. Motivasi perfect learning does not mediate environmental influences of school and peers on learning achievement. Based on these results, H8 and H10 were rejected, so for future studies other mediating variables can be examined.